(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Education is vital to achievement and development of every individual in this period of globalization. The impact of parent involvement on educational presentation has been noted worldwide. Therefore, it is important to examine factors that contribute to academic success of students. Aims and Objectives: Aim of this study was to analyze the effect of parental education and occupation on academic performance of medical student and to compare this effect in hostilites and day scholars. Material and Method: A sample of 200 first year students of Fatima Jinnah Medical University was selected for this study. Simple random sampling technique was employed in the selecting the sample from the targeted population. A questionnaire was used for gathering information about different factors related to academic performance of students. The quality of academic performance was measured by their achievement scores. Result: It was observed that 80-83% of hostilities belonging to highly educated and educated parents gained 50-70% marks.16-17% of hostilities belonging to educated parents gained > 70% marks. On the other hand 68% of hostilites belonging to less educated parents gained 50-70% marks followed by 24% getting> 70% marks. Conclusion: There exists a significant effect of parental education on academic performance of students. Among hostilites student’s academic performance related with their parent’s education was in a sequence of B, A and C. Among day scholar’s academic performance related with their parent’s education was in a sequence of A, C and B. It was also observed that the academic performance of hostilites was better than that of day scholars.